Claiming the right to rule: regime legitimation strategies from 1900 to 2019 - Marcus Tannenberg; Michael Bernhard; Johannes Gerschewski; Anna Lührmann; Christian von Soest (European Political Science Review, 2021)
Governments routinely justify why the regime over which they preside is entitled to rule. These claims to legitimacy are both an expression of and shape of how a rule is being exercised. In this paper, we introduce new expert-coded measures of regime legitimation strategies (RLS) for 183 countries in the world from 1900 to 2019. Country experts rated the extent to which governments justify their rule based on performance, the person of the leader, rational-legal procedures, and ideology. They were also asked to qualify the ideology of the regime. The main purposes of this paper are to present the conceptual basis for the measure, describe the data, and provide convergent, content, and construct validity tests for new measures. Our measure of regime legitimation performs well in all these three validation tests, most notably, the construct validity exercise which explores commonly held beliefs about leadership under populist rule.
Keywords: 300; legitimacy; legitimation strategies; expert survey; populism